Deglutição e aspectos nutricionais em idosos institucionalizados - Genehr, Simone de Souza (2022)
The aging process is the period of accentuation of morphophysiological limitations, which can predispose the individual to a state of greater vulnerability to pathologies and diseases, compromising the quality of life. In this sense, the epidemiological profile of the elderly population is characterized by multiple comorbidities, polypharmacy, and a high prevalence of mortality and morbidity, all resulting from conditions of exacerbation by the chronic disease. Additionally, alterations in the swallowing function can compromise the nutritional status and negatively affect the health conditions and life expectancy of the elderly. The objective of the present study was to evaluate and relate the characteristics of swallowing, nutritional and hematological status in institutionalized elderly people, in addition to comparing the groups according to life estimation scores. This is a cross-sectional, analytical, observational, uncontrolled study with 13 elderly people living in a long-stay institution (ILPI). Nutritional assessment was performed by measuring electrical bioimpedance, measurement of abdominal, calf, and arm circumferences, and measurement of the subscapular crease. Complementing the anthropometric measurements, a mini nutritional assessment (MNA®) was performed. To assess the muscle strength of the elderly, the hand grip strength test was performed. To assess swallowing, the speech therapy protocol for risk assessment for dysphagia (PARD) and the Eating Assessment Tool (EAT-10) were used. Finally, life expectancy was calculated using the age modified Charlson Comorbidity Index (ICCI). As a result, they were stratified into two groups by ICCI. In the group with high risk of mortality (n=8), overweight was highlighted in 5 (62.5%); cardiovascular risk in 4 (50%); malnutrition in 4 (50%) and risk for dysphagia in 3 (37.5%). While in the group with the lowest risk of mortality (n=5), 4 were overweight (80.0%); cardiovascular risk in 4 (80.0%); malnutrition in 1 (20.0%), and risk for dysphagia in 4 (80.0%), in addition, there were no statistical differences between the groups. Dynapenia 4 (50%) was found in the group with the highest risk of mortality (p=0.05). A negative and moderate association was found between MNA® and the risk for dysphagia (rho= - 0.59; p=0.03), moderate between MNA® and ICCI (rho=0.62; p=0.02), and a negative and strong relationship between risk of swallowing and HGS (rho - 0.67; p= 0.01). Therefore, the present study showed that institutionalized elderly people, with a high risk of mortality, had multimorbidity, overweight, dyspenia and risk for dysphagia. And older adults at higher risk for dysphagia were also at higher risk for malnutrition. The inclusion of the ICCI in a longstay institution can be a strategy for monitoring and establishing multidisciplinary care strategies.